EHD augmentation of convective boiling within a transparent heat exchange - McGranaghan, Gerard Joseph (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2013)
This work investigated the influence of electrohydrodynamic forces on the two-phase flow patterns of HFE7000 refrigerant under convective boiling conditions. A flow loop was constructed which featured two novel transparent heat exchanger designs which facilitated visualisation of the flow field under EHD and diabatic conditions. In both designs, a sapphire tube was employed which allowed heat transfer and optical access to the boiling refrigerant. A stainless steel rod within the sapphire tube formed a high voltage electrode, while a thin layer of Indium Tin Oxide (ITO), deposited on the tube exterior provided an optically transparent though electrically conductive transparent ground. High-speed video imaging was combined with thermal-hydraulic measurements to relate flow patterns with voltage. In Test Section A, the sapphire tube was surrounded by an acrylic channel through which heated water flowed, forming a transparent concentric heat exchanger. Heat transfer coefficients were calculated using thermocouples embedded in the sapphire tube wall and along the water side, and pressure drop was measured across the test section. A high speed camera recorded imagery along the test section length. In the first study, experiments were carried out at a refrigerant mass flux (G) of 100 kg/m2s, inlet qualities from 0-45%, heat input (Q//) of 12.4 kW/m2 and EHD voltage levels between 0 to 8 kV at 60Hz AC. It was found that at a constant heat flux of 12.4 kW/m2, EHD increased the heat transfer coefficients but with lower superheat temperatures. At 2% inlet quality an EHD voltage of 8 kV altered the flow regime from a stratified flow with nucleate boiling to a complex mixed flow with oscillating bubbles and liquid jets, resulting in improved heat transfer. It was also found that as quality increased, EHD voltages precipitated a flow regime change from stratified to annular, resulting in improved heat transfer. In the second study of tests at a constant water inlet temperature, the flow regime was seen to fall into three types dependent on EHD voltage. A base case was performed at 0 kV and voltage was increased in 1 kV increments. The first regime was of a stratified wavy flow with nucleate boiling, interspersed with occasional slugs which wet the top of the tube. The evaporation of this layer at the top provided lower thermal resistance and high heat transfer. As voltage was increased to 1 and 2 kV, bubble size increased and oscillations became apparent. Heat transfer rose by about 13% during this phase. As the voltage rose to between 3 to 6 kV, a new flow regime where occurred where liquid was extracted from the lower layer towards the electrode. Bubble diameter and oscillation increased further. At 6 kV the flow alternated between oscillatory entrained bubble flow and a flow of waves of cresting bubbles and liquid. These cresting events caused wetting of the top of the tube. EHD forces seemed to contribute to the upward movement and cresting of the large bubbles. This regime accounted for around 55% of the total heat transfer enhancement. At 7 kV another change appeared where liquid jets were produced and the flow began to alternate between the oscillating bubble and thin film regimes. In-tube flow was highly mixed, featuring droplets both from liquid jets and from bursting of the elongated bubbles. The top wall was highly wetted by the bubble bursting and cresting and this regime contributed 37% of the total heat transfer enhancement. Finally a third series of tests were conducted on Test Section B. This used an identical sapphire tube to Test Section A, but instead of water heating, the ITO coating on the tube exterior was thicker which permitted direct electrical heating. Thermocouples imbedded in the tube wall permitted local temperature measurements. On investigating the local heat transfer coefficients and flow patterns, it was found that EHD enhancement was higher at lower qualities and this was strongly linked to the higher liquid levels. EHD enhancement was also improved at higher qualities, but to a lesser level. The amount of liquid in proximity to the central electrode, and thus subject to higher EHD forces was central to high heat transfer enhancement. The magnitudes and profiles of the thermal measurements differed significantly from the water heated test section. This was mainly due to the upper temperature in the water heated section being limited, while the temperatures in the ohmically heated section had no such upper bound.
Keywords: Engineering, Ph.D.; Ph.D. Trinity College Dublin